1992
DOI: 10.1207/s15328023top1902_17
|View full text |Cite
|
Sign up to set email alerts
|

Some Lessons Learned about Teaching via Teleconference

Abstract: This article evaluates use of a teleconferencing system (the Optel Telewriter II©) to teach a senior level psychology course. The second author taught The Psychology of Thinking and Decision Making either on campus or via the telewriter. Multiple-choice examination scores were comparable for students in the telewriter and traditional lecture sections; however, telewriter students' course evaluations were less positive than those of on-campus students. The instructor's course ratings in subsequent sections of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…However, instructional methods must be modified to suit this approach. Also, because of the rapid development of computers and telecommunications, research findings can quickly become outdated 17,18 .…”
mentioning
confidence: 99%
“…However, instructional methods must be modified to suit this approach. Also, because of the rapid development of computers and telecommunications, research findings can quickly become outdated 17,18 .…”
mentioning
confidence: 99%
“…Non-traditional Student by Age. When reviewing the literature about remote site students, several studies showed results regarding the remote site student population being older (Biner et al, 1997;Collins and Pascarella, 2003; National Center for Educational Statistics report, 1999;Rosenthal, Mathews;and Stout 1992;Washburn-Hawkins, 1997;and Zarghami, 1998).…”
Section: Student Characteristicsmentioning
confidence: 99%
“…Reflection Back to Literature. General student characteristics among those at remote sites especially include a higher age (> 25 years old) than oncampus students placing them in the category of nontraditional students (Biner et al, 1997;Collins and Pascarella, 2003;the National Center for Educational Statistics, 1999;Rosenthal, Mathews, and Stout, 1992;Washburn-Hawkins, 1997;and Zarghami, 1997). With few exceptions distance is a gendered environment with regard to the student participants.…”
Section: Student Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation